Smart biotech learning media: A STEAM-IoT based to improve students’ problem-solving abilities and collaboration skills - Fajarani Fitriasih; Tri Handayani; Hanum Isfaeni (University of Muhammadiyah Malang, 2025)
Technological advances in the era of Learning Society 5.0 encourage the birth of innovation in education. One of them is Internet of Things (IoT) based learning media. This study aims to develop Internet of Things-based learning media with a STEAM approach to biotechnology material to improve problem-solving and collaboration skills in grade IX students. This type of research is educational design research using the ADDIE development model with stages of analysis, design, development, implementation, and evaluation. At the needs analysis stage, it was revealed that students needed learning media that had an attractive visual appearance and could be used anywhere. At the design and development stage, learning media was produced that was integrated with hydroponic devices directly through the Internet of Things. The product feasibility test was carried out by 3 material experts with an average score of 97.12% and 3 media experts with an average score of 89%. Based on the feasibility test, it is known that the learning media is very feasible to use. Educators and students evaluated the readability test and gave scores of 94.6 and 93.7 respectively, indicating that the learning media can be used as a biology learning medium. The results of the MANOVA test showed that the use of Internet of Things-based learning media with the STEAM approach successfully improved students' problem-solving and collaboration skills. Based on the results of the study, it can be concluded that Internet of Things-based learning media with the STEAM approach can be developed and is suitable as a learning medium for biotechnology materials, and is quite effective in improving students' problem-solving and collaboration skills.